Keratinocyte p38δ loss inhibits Ras‐induced tumor formation, while systemic p38δ loss enhances skin inflammation in the early phase of chemical carcinogenesis in mouse skin. Issue 5 (8th March 2015) - Kiss, Alexi; Koppel, Aaron C.; Anders, Joanna; Cataisson, Christophe; Yuspa, Stuart H.; Blumenberg, Miroslav; Efimova, Tatiana
Abstract : p38δ expression and/or activity are increased in human cutaneous malignancies, including invasive squamous cell carcinoma (SCC) and head and neck SCC, but the role of p38δ in cutaneous carcinogenesis has not been well‐defined. We have reported that mice with germline loss of p38δ exhibited a reduced susceptibility to skin tumor development compared with wild‐type mice in the two‐stage 7, 12‐dimethylbenz( a )anthracene (DMBA)/12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA) chemical skin carcinogenesis model. Here, we report that p38δ gene ablation inhibited the growth of tumors generated from v‐ras Ha ‐transformed keratinocytes in skin orthografts to nude mice, indicating that keratinocyte‐intrinsic p38δ is required for Ras‐induced tumorigenesis. Gene expression profiling of v‐ras Ha ‐transformed p38δ‐null keratinocytes revealed transcriptional changes associated with cellular responses linked to tumor suppression, such as reduced proliferation and increased differentiation, cell adhesion, and cell communications. Notably, a short‐term DMBA/TPA challenge, modeling the initial stages of chemical skin carcinogenesis treatment, elicited an enhanced inflammation in p38δ‐null skin compared with skin of wild‐type mice, as assessed by measuring the expression of pro‐inflammatory cytokines, including IL‐1β, IL‐6, IL‐17, and TNFα. Additionally, p38δ‐null skin and p38δ‐null keratinocytes exhibited increased p38α activation and signaling in response to acute inflammatory challenges, suggesting a role for p38α in stimulating the elevated inflammatory response in p38δ‐null skin during the initial phases of the DMBA/TPA treatment compared with similarly treated p38δ +/+ skin. Altogether, our results indicate that p38δ signaling regulates skin carcinogenesis not only by keratinocyte cell‐autonomous mechanisms, but also by influencing the interaction between between the epithelial compartment of the developing skin tumor and its stromal microenvironment. © 2015 Wiley Periodicals, Inc.